2020
DOI: 10.3389/fimmu.2020.608696
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Sepsis From Infection by Neutrophil Dysfunction: A Promising Role of CXCR2 Surface Level

Abstract: Sepsis is one of the well-established diseases with specific patterns of neutrophil dysfunctions. Previous studies demonstrated sepsis-related neutrophil dysfunctions in comparison with subjects without infection. Since sepsis and infection are recently recognized as distinctive processes, whether these neutrophil dysfunctions are associated with sepsis or infection are not known. Therefore, we longitudinally compared neutrophil functions, widely-cited as exhibiting sepsis-related changes, between patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Our study found that, in septic shock patients, most plasma-derived EVs are of non-leukocyte origins (i.e., platelet-EVs, erythrocyte-EVs, endothelial cells-EVs; ranked in descending order of plasma concentration). Interestingly, neutrophil-derived EVs only constitute a minority of plasma EVs despite the existing sepsis and infection-induced neutrophil dysfunctions ( 10 ) and previous publications highlighting the association between neutrophil EVs and the inflammatory process of sepsis ( 26 , 27 ). These findings emphasize an important role of blood cells of non-leukocyte origin in modulating and propagating the hyperinflammatory reactions of sepsis and infection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study found that, in septic shock patients, most plasma-derived EVs are of non-leukocyte origins (i.e., platelet-EVs, erythrocyte-EVs, endothelial cells-EVs; ranked in descending order of plasma concentration). Interestingly, neutrophil-derived EVs only constitute a minority of plasma EVs despite the existing sepsis and infection-induced neutrophil dysfunctions ( 10 ) and previous publications highlighting the association between neutrophil EVs and the inflammatory process of sepsis ( 26 , 27 ). These findings emphasize an important role of blood cells of non-leukocyte origin in modulating and propagating the hyperinflammatory reactions of sepsis and infection.…”
Section: Discussionmentioning
confidence: 94%
“…The result gained from this design is a mixed effect of infection and sepsis rather than sepsis itself. As pointed out by the latest sepsis definition (2) and demonstrated by a published work of our group (10), immune alterations that occurred in sepsis and infection differ and should be addressed by the study design. In addition, the cross-sectional nature of previous studies omits the dynamicity of sepsis; hence, their results may not be able to apply to patients presenting at different time points during the disease course.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple causative mechanisms for aberrant neutrophil migration with both the neutrophil and the endothelium shown to be altered in the diabetic microenvironment. Internalisation of the chemokine receptor CXCR2 was associated with reduced migration in a study of sepsis in mice with alloxan induced diabetes, which is a shared neutrophil dysfunction mechanism common to non-diabetes sepsis models ( 107 , 110 ). CXCR2 expression is downregulated by TLR2 signalling, which involves G protein coupled receptor kinase-2 (GRK2) ( 111 ).…”
Section: Neutrophil Recruitment and Chemotaxismentioning
confidence: 99%
“…We believe that our i-BID platform, performed on basophils, has strong potential to accelerate immune functional assays for this cell type, such as the basophil activation test for allergy assessment ( 24 ). It will also be of interest to apply the i-BID platform to isolate other cell types, such as neutrophils to investigate their dysfunction for sepsis diagnosis ( 68 ), or T-cells for enzyme linked immunosorbent assay (ELISA)-based interferon-gamma (IFN- γ ) release assays for tuberculosis diagnosis ( 69 ).…”
Section: Discussionmentioning
confidence: 99%